ANALISIS KELENGKAPAN PENGISIAN REKAM MEDIS PASIEN RJ POLI UMUM GUNA MENUNJANG MUTU REKAM MEDIS - Halsa Imas Halimatusaadah; Meira Hidayati (Politeknik Negeri Jember, 2022)
Medical records are documents that contain data or patient history. The completeness of filling out medical records at the UPTD (Regional Technical Implementation Unit) of the Haurwangi Health Center is only 70%. The purpose of this study was to analyze the completeness of filling out outpatient medical records at the UPTD of the Haurwangi Health Center in order to support the quality of medical records. The type of research used is descriptive research using quantitative analysis and data collection techniques using observation, interviews, and literature review. The sample used was 71 medical record documents in May 2021. The study of incomplete found in patient identification is 10% or 7 outpatient medical record documents, in important reports 8% or 6 outpatient medical record documents, in authentication reviews 11 % or 8 outpatient medical record documents. The conclusion based on the quality calcutation of the completeness of filling out medical records using the KLPCM formula (Incomplete Filling of Medical Records) there are 30% incomplete medical records and medical records cannot be said to be of good quality. Suggestions from researchers are to evaluate, socialize, and monitor the SOP (Standard Operasional Procedures) for the completeness of outpatient medical records at the Haurwangi Health Center UPTD